Carbohydrate contents and some growth of Curcuma alismatifolia in response to low night temperature treatment - Hongpakdee P. (International Society for Horticultural Science, 2014)
Decreasing of the night temperature in greenhouse during off-season production is a factor leading to the reduction of growth and flower quality in Curcuma alismatifolia. The effect of low night temperature on carbohydrate contents and some growth parameters in this plant was thus determined. Plants were grown under 30/24°C day temperature/night temperature (DN/TN) as high night temperature (HNT) or under 30/18°C as low night temperature (LNT) with 13 hour day-length. The humidity and light levels were maintained at 70-80% RH and 270 μmol m-2 s-1, respectively. Plant samples were harvested at flowering stage (12 weeks after planting). The results showed that glucose and fructose accumulation in leaf and storage roots were significantly decreased under LNT. Nevertheless, carbohydrate contents in rhizomes were not affected by LNT. The HNT treatment led to better plant growth in terms of total leaves area, leaves dry matter, rhizomes dry matter and number of shoots per clump. LNT increased rhizomes dry matter.